Asymmetric synthesis of aminocyclooctenecarbonitriles: Cyclooctene β-lactam and hydroxyaminocyclooctene carboxylic precursors. Issue 3 (17th January 2019) - Aydin, Busra Ozturk; Yurtoglu, Emine; Arcelik, Nejat; Sahin, Ertan; Secen, Hasan; Altundas, Ramazan
Graphical abstract: Highlights: Enantiopure aminocyclooctene carbonitriles were accessed in g quantity. New unsaturated β-lactams were achieved. Hydroxyaminocyclooctene carbonitriles were obtained via aziridine ring opening. The absolute stereochemistry of the synthesized compounds was determined by X-ray. Abstract: Enantiopure β-aminocyclooctenenitriles, as precursors of β-amino acids and β-lactams, were synthesized from a readily available chloroalkene nitrile and ( S )-methylbenzylamine via a straightforward substitution reaction and purified by crystallization. Acidic hydrolysis of the nitrile groups to their corresponding amides followed by DCC assisted carbonyl group activation gave novel α, β-unsaturated lactams. The treatment of 3-bromo-8-chlorocyclooctenecarbonitrile with ( S )-methylbenzylamine furnished a diastereomeric mixture of bromoaminocyclooctenecarbonitriles via an S N 2′ pathway rather than bromide substitution via an S N 2 pathway. The diastereomeric mixture of bromoaminocyclooctanecarbonitriles provided two novel aziridines upon heating. TFA catalyzed aziridine ring opening gave γ-hydroxyl-β-aminocyclooctenecarbonitriles and γ-amino-β-hydroxycyclooctenecarbonitriles.